2022
DOI: 10.5545/sv-jme.2021.7364
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Erosion Modelling on a Radial Divergent Test Section Using RANS

Abstract: Cavitation is the phenomenon of fluid evaporation in hydraulic systems, which occurs due to a pressure drop below the value of the vapor pressure. For numerical modeling of this generally undesirable phenomenon, which is often associated with material damage (erosion), there are various mathematical vapor transfer models that have been validated in the past. There are different approaches to predicting cavitation erosion, which have mostly been experimental in the past. Recently various numerical models have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Melissaris et al [31] derived two alternative formulations for Dα v Dt − and concluded that the formulation where the total derivative of vapour volume fraction is expressed with the cavitation sink term is the most accurate, which was also confirmed by our previous work [47].…”
Section: Cavitation Erosion Risk Indicatorssupporting
confidence: 66%
“…Melissaris et al [31] derived two alternative formulations for Dα v Dt − and concluded that the formulation where the total derivative of vapour volume fraction is expressed with the cavitation sink term is the most accurate, which was also confirmed by our previous work [47].…”
Section: Cavitation Erosion Risk Indicatorssupporting
confidence: 66%